PENGUATAN PEMBELAJARAN INTERAKTIF MELALUI WORKSHOP IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI PADA GURU SMA NEGERI 2 NARMADA - Dinda Juliana Novita; Rosa Yuniarti; Jepri Utomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores the implementation of technology-based learning media as an innovative approach in the educational process at SMA 2 Narmada. Following the Kampus Merdeka initiative launched by the Minister of Education and Culture, the study identifies challenges faced by teachers in integrating digital technology into their teaching practices. A one-day workshop was conducted to enhance teachers' knowledge and skills in utilizing various educational tools and platforms. The workshop aimed to create a more engaging learning environment, ultimately improving student motivation and academic performance. Results indicate that increased confidence in using technology among educators leads to more interactive and effective teaching methods.